Territorial-industrial cluster in the concept of sustainable development of a region (by the example of Volga federal district) - R. R. Valeeva; V. L. Vasilyev (Russian Journal of Economics and Law)
Objective: to reveal the points of contact and dependence between a territorial-industrial cluster and the sustainable development of the region where the cluster is located.Methods: multi-dimensional comparative analysis, method of Euclidian distances. Results: the work reveals the issues of influence of territorial-industrial clusters on the sustainable development of a region. The factors of sustainable development are studied, as well as the influence of territorial-industrial clusters on them. The analysis of scientific research of the issue of regional development showed that the main trend of scientific research is the study of ecological, managerial and methodological aspects. The authors conclude that the interdependence between clusters and the social-economic development of a region is understudied.To achieve the research goals, the regions of the Volga Federal District were estimated by economic, social and ecological indicators. The calculations were made under methodology by T.V. Uskova, modified and supplemented by the authors. Basing on the calculation of the integral index of sustainability of VFD regions, it was found that all regions within the studied period were in the zone of development; the most stable are the Republics of Tatarstan and Bashkortostan and Perm krai. Also, the integral indicators were compared to the number of clusters in the regions; it was found that the highest sustainability of the indicators are shown by the regions where the clusters are located. A time lag of one year was noticed between a new cluster appearance and the integral index growth.Scientific novelty: for the first time, basing on the element composition of the sustainable development of a region, the role of a territorial-industrial cluster is determined for each factor; the methodology of estimating the sustainable development of a region is improved; the indicators of the sustainable development of a region are compared with the presence of territorial-industrial cluster in these regions.Practical significance: the main provisions and conclusions of the article may be used in scientific and educational activity when considering the issues of clusters and sustainable development of regions.